The impact of CTLA-4 blockade and interferon-α on clonality of T-cell repertoire in the tumor microenvironment and peripheral blood of metastatic melanoma patients. (2nd November 2019) - Khunger, Arjun; Rytlewski, Julie A.; Fields, Paul; Yusko, Erik C.; Tarhini, Ahmad A.
ABSTRACT: Patients with metastatic melanoma were treated with tremelimumab and interferon-α (IFN) in a previously reported clinical trial [NCT00610857]. Responses were assessed by RECIST criteria as complete (CR) or partial (PR), stable disease (SD) or progressive disease (PD). In this study, T-cell receptor (TCR) beta-chain repertoire was immunosequenced in peripheral blood mononuclear cells (PBMC) specimens (N = 33) and tumor samples (N = 18) utilizing the immunoSEQ® Assay to determine repertoire clonality and T cell fractions at pre-treatment (tumor and PBMC), one month (PBMC) and 3 months (PBMC) time points and evaluate its association with clinical outcomes. In the pretreatment tumor microenvironment (TME), T cell clonality was significantly ( p = .035) different and greater in patients who achieved disease control (CR, PR, SD) versus those with non-disease control (PD) as best response to treatment. Further, there was significantly ( p = .001) increased TCR fraction in tissue of responders (CR, PR) versus non-responders (PD, SD). In examining T cell clonality in the circulation (PBMC), no significant associations were found in the pretreatment samples. However, early on-treatment (4 weeks) there was a significant decrease in T cell clonality that was associated with improved overall survival ( p = .01) and progression-free survival ( p = .04). In addition, analysis of temporal changes in tumor-infiltrating lymphocytes (TIL) and peripheral TCR repertoire revealed that responders had significantly higher clonal expansion of TIL in the circulation at 4 weeks than non-responders ( p = .036). Our study provided interesting mechanistic data related to CTLA-4 Blockade and IFN and potential biomarkers of immunotherapeutic benefit.